UMUR SIMPAN DAN UJI HEDONIK KUE SUS SUBSTITUSI TEPUNG GANYONG - Purba, Lilis Pratiwi; Elida, Elida; Faridah, Anni; Anggraini, Ezi (Ensiklopedia of Journal, 2025)
Abstract: This research is motivated by previous studies on choux pastry substituted with ganyong flour, but no studies have examined the shelf life and panelists' preference levels, both for control choux pastry and 45% ganyong flour substitution. The purpose of this study was to analyze the shelf life and hedonic test as a local tuber-based food innovation. The method used was a mixed method with a qualitative approach (shelf life observation) and quantitative (hedonic test by 50 untrained panelists) on the attributes of color, texture, aroma, and taste. Data analysis used Paired Sample t-Test with t-table = 1.976 (α = 0.05; df = 149). The results showed that the maximum shelf life of control and substitution choux pastry was two days at room temperature (23–29°C). The hedonic test showed significant differences in aroma (t = 3.227), inner texture (t = 2.146), and taste (t = 2.742), but not significant in outer color, inner color, and outer texture. The substitution of ganyong flour has a significant impact on several specific sensory attributes, especially aroma and taste, and has the potential to be further developed by improving the formulation and processing technology to produce a more optimal and widely accepted productKeywords: Choux Paste, Canna Flour, Shelf Life, Hedonic Test.